Local Deformation of Glasses is Mediated by Rigidity Fluctuation on Nanometer Scale - Benzine, Omar; Bruns, Sebastian; Pan, Zhiwen; Durst, Karsten; Wondraczek, Lothar (Advanced Science, 2018)
Microscopic deformation processes determine defect formation on glass surfaces and, thus, the material's resistance to mechanical failure. While the macroscopic strength of most glasses is not directly dependent on material composition, local deformation and flaw initiation are strongly affected by chemistry and atomic arrangement. Aside from empirical insight, however, the structural origin of the fundamental deformation modes remains largely unknown. Experimental methods that probe parameters on short or intermediate length-scale such as atom–atom or superstructural correlations are typically applied in the absence of alternatives. Drawing on recent experimental advances, spatially resolved Raman spectroscopy is now used in the THz-gap for mapping local changes in the low-frequency vibrational density of states. From direct observation of deformation-induced variations on the characteristic length-scale of molecular heterogeneity, it is revealed that rigidity fluctuation mediates the deformation process of inorganic glasses. Molecular field approximations, which are based solely on the observation of short-range (interatomic) interactions, fail in the prediction of mechanical behavior. Instead, glasses appear to respond to local mechanical contact in a way that is similar to that of granular media with high intergranular cohesion.
CRIS-Team Scopus Importer:2023-04-20
Keywords: deformations; flexible substrates; glass; heterogeneity; silica; strength